A study on the forming analysis of a self-reinforced polypropylene based composite-aluminium hybrid structures. - Sivakumar, Dhar Malingam (2010)
This study investigates the effects of blank temperature, feed rate and blank holder force on the formability of hybrid structures made of self reinforced polypropylene and aluminium also known as Fibre-Metal Laminates (FML). Feed rate was found to be the dominant factor governing the formability of this class of material. Temperatures and blank holder force were deemed to be important for achieving high quality of the parts manufactured. Comparisons between FML and monolithic aluminium revealed that FML possess better formability characteristics than monolithic aluminium. Moreover FML gives a 27% weight reduction compared to monolithic aluminium. Comparison between FML and monolithic aluminium surface strain results show FML system having a more uniform strain distribution further enhancing the quality of the final part using this class of material. Furthermore the work required to form FML is 30% less than for monolithic aluminium. The experimental results obtained in the present study shows FML systems have the potential to be adapted to high volume production technique of stamp forming.